Constituição, democracia e capitalismo: Otto Kirchheimer e Franz Neumann sob Weimar - Henrique Pereira de Queiroz (2023)
The present work seeks to carry out a theoretical reconstruction of the main texts of the jurists Franz Neumann and Otto Kirchheimer on and in the period of the Constitution of the Weimar Republic, adopting as a central focus to comparatively highlight the way in which the contradiction between democracy and capitalism was placed in them. In this way, the challenge presents itself exactly in the sense of identifying the emancipatory potentials and limits of the Law and the Constitution in a social democracy. Between the critique of capitalist society and the defense of the minimum of freedom and equality guaranteed by constitutional democracy, the authors offer an instigating and complex theoretical reflection that escapes, at the same time, from an apology to the bourgeois liberal vision, as well as a functionalist approach to Law. At the end of the work, it will be possible to present how the theoretical reconstruction of part of the works of these authors is still important for understanding the irreconcilable character between a deeper sense of democracy and the capitalist mode of production, a tension that is located internally to the modern Constitution. At the same time, it will also be possible to assert, through the work of these authors, emancipatory potentials already present in social-democratic constitutionalism itself, which point to the critique and overcoming of the society founded under this capitalist economic system.